2016
DOI: 10.1039/c6ra05032h
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of battery performance of LiMn2O4: correlations between electrochemical and magnetic properties

Abstract: We report the results of a systematic investigation of structural, electrical transport, magnetic, and electrochemical properties of LiBxMn2−xO4 (where x = 0.0–1), synthesized via a one-step solid state reaction technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 86 publications
0
8
0
Order By: Relevance
“…Further, it has been noticed that such Jahn–Teller-like distortion has a pronounced effect on the electrochemical properties. For instance, Demirel et al reported the enhanced capacity of LiMn 2 O 4 due to the suppression of Jahn–Teller distortion while substituting Mn 3+ with another element. Further, the existence of Jahn–Teller distortion in LiNiO 2 has led to the instability of the cathode material .…”
Section: Discussionmentioning
confidence: 99%
“…Further, it has been noticed that such Jahn–Teller-like distortion has a pronounced effect on the electrochemical properties. For instance, Demirel et al reported the enhanced capacity of LiMn 2 O 4 due to the suppression of Jahn–Teller distortion while substituting Mn 3+ with another element. Further, the existence of Jahn–Teller distortion in LiNiO 2 has led to the instability of the cathode material .…”
Section: Discussionmentioning
confidence: 99%
“…This points to different proportions of high and low spin configurations within the produced Mn 3+ states in uncoated and VO x -coated samples. Generally, Mn 4+ and Mn 3+ in octahedral coordination are both in high spin (HS) configuration, with the latter showing a higher spin state. The HS Mn 3+ Jahn–Teller active phase has been correlated to the capacity loss in spinel LiMn 2 O 4 , with the Jahn–Teller distortions destabilizing the structure during electrochemical cycling. The strong μ Mn drop upon charge in the uncoated material suggests the formation of a Mn environment corresponding to that of layered rhombohedral r -LiMnO 2 , where theoretical calculations predict the Mn 3+ in the not Jahn–Teller active low spin (LS) configuration . Interestingly, the theoretical simulation of this phase predicts several potential advantages for a good electrochemical activity and agrees with the results reported here, in fact it explains the shift of the main Mn K-edge absorption feature toward higher energy during the charge, generally associated with oxidation, while Mn is actually partially reducing.…”
mentioning
confidence: 99%
“…Susceptibility of the samples increases with increasing Ru content and the transition temperature gradually shifts from ~150 K to ~170 K. μ eff values of the samples were calculated by the linear part of χ −1 ‐T graph as seen in Figure B. Details of μ eff calculation procedure can be found in ref . The calculated μ eff and theta values are listed in Table .…”
Section: Resultsmentioning
confidence: 99%